Canine Adenovirus 2: A Natural Choice for Brain Circuit Dissection - Lavoie, Andréanne; Liu, Bao-hua (Frontiers in Molecular Neuroscience, 2020)
Canine adenovirus-2 (CAV) is a canine pathogen that has been used in a variety of applications, from vaccines against more infectious strains of CAV to treatments for neurological disorders. With recent engineering, CAV has become a natural choice for neuroscientists dissecting the connectivity and function of brain circuits. Specifically, as a reliable genetic vector with minimal immunogenic and cytotoxic reactivity, CAV has been used for the retrograde transduction of various types of projection neurons. Consequently, CAV is particularly useful when studying the anatomy and functions of long-range projections. Moreover, combining CAV with conditional expression and transsynaptic tracing results in the ability to study circuits with cell- and/or projection-type specificity. Lastly, with the well-documented knowledge of viral transduction, new innovations have been developed to increase the transduction efficiency of CAV and circumvent its tropism, expanding the potential of CAV for circuit analysis.